To identify the solution for the system of equations, we need to find the point where the two equations intersect, which means we need to look for a pair (x, y) that appears in both equations.
From the provided table:
-
For \(x = 0\):
- \(y = 2(0) - 5 = -5\)
- \(y = 0 - 3 = -3\)
-
For \(x = 1\):
- \(y = 2(1) - 5 = -3\)
- \(y = 1 - 3 = -2\)
-
For \(x = 2\):
- \(y = 2(2) - 5 = -1\)
- \(y = 2 - 3 = -1\)
-
For \(x = 3\):
- \(y = 2(3) - 5 = 1\)
- \(y = 3 - 3 = 0\)
The only pair (x, y) that has the same y-value for both equations is (2, -1).
Thus, the solution for the system is \((2, -1)\).
-response: (2,−1)